PENGARUH INSENTIF TERHADAP KINERJA KARYAWAN BAGIAN OPERASIONAL PADA PT. BPR UNISRITAMA, PEKANBARU - Ramadhan, Romal; ", Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
In an effort to improve employee work, companies need to pay attention to employee welfare, one of which is by providing incentives as a form of encouragement and reward from employees' work results while working. This research was conducted at PT BPR Unisritama, Pekanbaru which is located at Soekarno Hatta Street, Pekanbaru, Riau Province. This research aims to determine the effect of Incentives on Employee Performance at PT BPR Unisritama, Pekanbaru working in the operational field. This study uses quantitative descriptive analysis method with SPSS program. The sample in this study is a number with a research population of 39 people using census methods that are distributed to all employees of the operational section at PT BPR Unisritama, Pekanbaru. The analysis tools in this study use validity test, reliability test, simple linear regression analysis, determination analysis and significance test with t test. This study showed that incentive variables had an impact on employee performance of 16,428 with a signification rate of 0.000. Based on the results of determination known coefficient of determination of 0.879 with the sense that the contribution of incentive variable influence on employee performance in the operational section of PT BPR Unisritama, Pekanbaru is 87.9% while the remaining amount of 13.1% is influenced by other variables not discussed in this study. Â